Can Critical Velocity in young swimmers be determined by a 10x25m all-out swimming test? - Morgado, J. P.; Curto, D.; Matias, C. N.; Monteiro, C. P.; Alves, F. B.; Reis, J. F. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: In swimming, Critical Speed (CS) is considered one of the key markers of aerobic capacity, which is important for monitoring training and competition. Recently, a 12x25m all out test was validated for CS determination in elite swimmers, a proxy of the 3 min all out test validated for other exercise modalities [1]. In young swimmers it may be pertinent to adjust the test to 10x25m so that the total duration approaches 3 min due to the lower maximal speed of the younger swimmers [2]. Our aim was to compare the CS calculated from the 10x25m with the traditional method using 200 and 400m efforts.